2020
DOI: 10.1556/2006.2020.00010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory control and problematic Internet-pornography use – The important balancing role of the insula

Abstract: Background and aims Diminished control over a specific behavior is a core characteristic in addictive behaviors such as problematic Internet-pornography (IP) use. First studies suggest that a hyperactivity of the impulsive system is one reason for impulsive behaviors in the context of problematic IP use. The tripartite-process theory of addiction explains neurocognitive mechanisms beyond common dual-process theories in addictive behaviors. However, the role of the reflective and interoceptive system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
(177 reference statements)
0
17
0
Order By: Relevance
“…However, studies of self-regulatory capacities found in this review rather assessed general self-rated self-control. Given the relative importance of response inhibition for several addictive behaviors, such as pornography viewing (e.g., Antons & Brand, 2020), gaming (e.g., Argyriou et al, 2017), gambling (e.g., Lawrence et al, 2009), or buying-shopping (e.g., Trotzke et al, 2020), future research is needed to investigate the potential impact that mindfulness techniques may have on stimulus-specific inhibitory control in the context of nonsubstance addictive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of self-regulatory capacities found in this review rather assessed general self-rated self-control. Given the relative importance of response inhibition for several addictive behaviors, such as pornography viewing (e.g., Antons & Brand, 2020), gaming (e.g., Argyriou et al, 2017), gambling (e.g., Lawrence et al, 2009), or buying-shopping (e.g., Trotzke et al, 2020), future research is needed to investigate the potential impact that mindfulness techniques may have on stimulus-specific inhibitory control in the context of nonsubstance addictive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Antons and Brand (2018) found that higher symptom severity of cybersex addiction was related to higher trait impulsivity interaction with more impulsive actions. However, another study found that individuals with more symptoms of cybersex addiction exhibited better BIC performance (Antons & Matthias, 2020).…”
Section: Impulsivity In Cybersex Addictsmentioning
confidence: 95%
“…The ability to suppress inappropriate behavior is a main function of the reflecting system, the impairment of which was proposed as a key determinant for uncontrolled internet and drug use (Volkow et al, 2010;Brand et al, 2019). The reflecting system in IA and substance addiction was consistently found to be dysfunctional when performing inhibition control tasks (Darnai et al, 2019;Antons and Matthias, 2020;Suarez-Suarez et al, 2020); therefore, it was regarded as a therapeutic target for addiction. After noninvasive treatment targeted to the system, the addiction symptoms were significantly relieved (Newman-Norlund et al, 2020;Su et al, 2020), indicating the critical role of the reflective system in addiction.…”
Section: Hypoactive Reflecting Systemmentioning
confidence: 99%